Effect of ammoniated rice straw with urine and urea on the amount of digested crude protein, methane gas production and VFA profile of fat tail sheep - Wahyu Subagio Saputro; Kabib Efendi; Sitta Noratuada Aurashka; Novita Alvita Sarie (Universitas Sebelas Maret, 2024)
Objective: This research aimed to find out the VFAs profile and methane gas production in fat-tailed sheep that fed rice straw ammoniated with commercial urea (T1), and rice straw ammoniated with urine (T2). Eight thin-tailed sheep aged 1.5 with an average body weight of 20 kg were used in this study. All the object studies were placed in individual metabolism cages. The feed concentrate used in this study was 2.3 % from the body weight of livestock, rice straw was ammoniated and water was given ad libitum, and feed was given twice a day at 7.00 a.m. and 4.00 p.m. Concentrate were given first, then 1 hour later the ammoniated rice straw was given. The drinking water was provided ad libitum.Methods: This research was conducted in three stages, 1) total collection, 2) measure methane gas production, and 3) rumen fluid collection. A completely randomized design with 2 treatments and 4 replications was used in this study. After all data was collected, then it was analyzed using the Independent T-test using IBM SPSS Statistics 21 software.Results: The results show no significance (P > 0.05) on rice straw ammoniated with commercial urea (T1), and rice straw ammoniated with urine (T2) for methane gas production (1,328.68±349.56 vs 1,463.95±215.41), VFA Total (40.74±13.09 vs 34.79±6.34), NH3 production (9.17±3.67 vs 8.78±2.94). It indicates that ammoniated using commercial urea or urine does not interrupt rumen fermentation.Conclusions: It could be concluded that crude protein digestible, methane gas production, and VFAs profile especially the fermentation conditions in the rumen are not affected by ammoniation from commercial urea or urine.